Impact of climatic variations on the abundance pattern of Perkinsiella saccharicida in the ingenio sugar San Carlos, Ecuador - Edwin Jiménez-Ruiz; Mariela González-Narváez; Víctor Puente-Tenezaca; Óscar Nuñez-Burgos; William Fonseca-González; Carlos Ordóñez (Scientific Reports)
Abstract Global warming, produced by the accumulation of greenhouse gases in the atmosphere, is causing alterations in the life cycle of flora and fauna species and consequently threatening food security. The objective of this research was to study the relationship between climatic variables and the incidence and presence of Perkinsiella saccharicida populations, a sucking insect considered a pest, that attacks sugarcane crops depending on the climatic season. This study was carried out in sugarcane plantations of Ingenio San Carlos, located in Marcelino Maridueña, Ecuador. We analyzed climatic data and Perkinsiella population records from 2006 to 2023, applying various parametric (KS, ANOVA, Bartlett, Dickey-Fuller) and non-parametric (Spearman, Shapiro, Kruskall-Wallis, Levene) statistical tests, along with CCF and causality analysis. The findings revealed that the current summer averages of atmospheric variables have increased and are now comparable to winter averages from ten years ago. High temperatures and Solar_R values were found to precede Perkinsiella population spikes by 6 months. A causal relationship was established between specific atmospheric variables and Perkinsiella. Initial outbreaks were observed during the summer, with population sizes increasing over time. Currently, there is a tendency for the pest to persist throughout the year (winter-summer), necessitating greater biological and chemical control measures to manage populations.